The comparison of the prevalence, awareness, treatment and control of hypertension among adults along the three provinces of the Lancang-Mekong River countries-China, Laos and Cambodia - Huadan Wang; Liping He; Min Ma; Mingjing Tang; Jiang Lu; Labee Sikanha; Sokha Darapiseth; Manli Sun; Teng Wang; Zhongjie Wang; Yu Xia; Qiuyan Zhu; et al. (BMC, 2024)
Abstract Background Under the background of similar geography and culture in Lancang-Mekong countries and rapid changes in the regional economy and lifestyle, this study aimed to describe and compare the prevalence, awareness, treatment, and control of hypertension and assess the hypertension care cascade in three provinces of China, Laos, and Cambodia. Methods A cross-sectional study was conducted between 2021 and 2023 in the three provinces of Lancang-Mekong River countries using consistent investigative procedures. We included 11,005 participants aged ≥ 18 years from three provinces, and data were collected through questionnaires, physical examinations, and biochemical tests. We analyzed the cascade of hypertension care and compared the prevalence, awareness, treatment, and control of hypertension. Results The hypertension care cascade indicated that 46.3%, 51.6%, and 63.1% of patients in Yunnan Province (China), Oudomxay Province (Laos), and Ratanakiri Province (Cambodia), respectively, were not diagnosed, and 10.7%, 12.8% and 21.1% of patients, respectively, did not receive treatment. After sex-age standardization, the prevalence rates of hypertension in the three provinces were 33.4%, 34.5%, and 23.6%, respectively. Higher awareness rate in Yunnan Province (53.4%) and Oudomxay Province (46.5%) than in Ratanakiri Province of Cambodia (39.7%). The treatment rate of hypertension in Yunnan Province (42.4%) was higher than that in Oudomxay Province (34.5%), and Ratanakiri Province (16.9%). In addition, less than 20% of the patients in the three provinces had their blood pressure under control. The factors associated with hypertension differed across the three provinces. Conclusions In the three provinces of the Lancang-Mekong River Basin countries, there is a high burden of hypertension and a significant unmet need for hypertension care. Targeted and precise intervention strategies are urgently needed to improve the awareness, treatment, and control of hypertension in low- and middle-income regions. Graphic Abstract